Health Professionals Who Suffer Intimate Partner Violence: A Descriptive, Multicenter, and Cross-Sectional Study. Issue 1 (January 2019) - Carmona-Torres, Juan Manuel; Cobo-Cuenca, Ana Isabel; Recio-Andrade, Beatriz; Dios-Guerra, Caridad; Lopez-Soto, Pablo Jesús; Hidalgo-Lopezosa, Pedro; Rodríguez-Borrego, María Aurora
ABSTRACT: Objective: The purpose of this study was to know who are the people who assist women, who work as a health professional in the Spanish Public Health System, when they suffer intimate partner violence (IPV). Methods: A descriptive, cross-sectional, multicenter study was conducted. The participants were female health professionals ( N = 794) working within the Spanish Public Health System. The instrument used was Delgado, Aguar, Castellano, and Luna del Castillo's (2006) scale to measure ill-treatment of women. Results: Two hundred seventy women suffered IPV (34%). Of the female health professionals who suffered IPV, 25.9% had spoken with someone about the violence, most commonly talking to trusted people (24.3%), a psychologist (24.3%), health professionals (20%), and others (20%). Married female health professionals living with their current or last partner/husband, residing in an urban area, and with their own salary were least likely to speak about their problem. Conclusion: Female health professionals who suffer IPV usually speak about this problem with trusted people instead of consulting a health professional, which may leave the problem in the private sphere. This can be because of victims not wanting to report the violence for fear of their intimate partner or wanting it to remain private. This may deprive the victims of the help they need. For this reason, the health services should establish screening for IPV not only for their patients but also for their workers.